Remarks at Media Roundtable during Annual Meetings 2019 - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, fielded questions from the media. He spoke about fundraising for the nineteenth replenishment of IDA. He explained the importance of debt transparency. He discussed the World Bank's role in Ukraine in terms of land reform, the reform of the financial system, reform of state-owned enterprises, reform of the of Ukraine's fiscal structure, and related issues. He discussed the Bank’s work on climate change and the environment. He highlighted the sluggish growth of investment in developing countries, but with good policies, countries can find a way to go against the trend and improve their growth outlook. He commented on trade facilitation and trade integration in Africa. He cautioned about the slowness of world trade growth and its implications on developing countries.